2021
DOI: 10.1097/icl.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Increased Screen Time and Dry Eye: Another Complication of COVID-19

Abstract: During a time of relative social isolation because of the coronavirus disease 2019 (COVID-19) virus, electronic devices have enabled people to continue to work, learn, and socialize. The long-term effects of this increase in electronic device use on physical and mental health are unknown and will take years to determine. Before COVID-19, the negative effect of prolonged screen time on the health of the ocular surface was known 1 and the increased use of electronic devices necessitated by the pandemic will exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
0
16
0
4
Order By: Relevance
“…In adults, increases in screen time was consistently associated with dry eye syndrome, which broadly agrees with previous literature in both a COVID-19 and non-COVID-19 context. 120,121 It was also found that more than 6 h of screen time/day was associated with several symptoms of digital eye strain, including tearing, eye strain, dryness, heavy eyelids, red eyes, eye itchiness, burning sensation in the eye, sensitivity of bright light, difficulty focussing, eye pain, the feeling of a foreign body in the eye, and excessive blinking. These results concur with pre-pandemic reviews that have found associations between dry eye syndrome and screen time.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, increases in screen time was consistently associated with dry eye syndrome, which broadly agrees with previous literature in both a COVID-19 and non-COVID-19 context. 120,121 It was also found that more than 6 h of screen time/day was associated with several symptoms of digital eye strain, including tearing, eye strain, dryness, heavy eyelids, red eyes, eye itchiness, burning sensation in the eye, sensitivity of bright light, difficulty focussing, eye pain, the feeling of a foreign body in the eye, and excessive blinking. These results concur with pre-pandemic reviews that have found associations between dry eye syndrome and screen time.…”
Section: Discussionmentioning
confidence: 99%
“…Such smart work models have resulted in the creation of new lifestyles, digital work and digital schooling, and limit young people and adults to long-term near-visual work. However, long-term use of VDTs may disrupt the surface of the eye, resulting in conditions such as DED ( 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, during the COVID-19 era, several publications suggested an increased incidence of dry eye due to lockdown related environmental changes, including mask use, increased use of screens, and dietary deficiencies. [29][30][31] https://doi.org/10.2147/OPTH.S343793…”
Section: Discussionmentioning
confidence: 99%